2008
DOI: 10.1093/cercor/bhn225
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in the Effects of Acute and Chronic Stress and Recovery after Long-Term Stress on Stress-Related Brain Regions of Rats

Abstract: Studies show that sex plays a role in stress-related depression, with women experiencing a higher vulnerability to its effect. Two major targets of antidepressants are brain-derived neurotrophic factor (BDNF) and cyclic adenosine monophosphate response element–binding protein (CREB). The aim of this study was to investigate the levels of CREB, phosphorylation of CREB (pCREB), and BDNF in stress-related brain regions of male and female rats after stress and recovery. CREB and pCREB levels were examined in CA1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(58 citation statements)
references
References 83 publications
(96 reference statements)
6
52
0
Order By: Relevance
“…Our fi ndings are consistent with the idea that female hormones that regulate production of corticotrophin-releasing factor can play the key role in hyperactivity of the hypothalamic-pituitary-adrenal axis, while changes in their level determine the severity of the stress reaction and is a risk factor for depression development [15]. Worse learning of experimental females in comparison with experimental males can be associated with higher sensitivity of females to the development of depression-like behavior [14].…”
Section: Resultssupporting
confidence: 88%
“…Our fi ndings are consistent with the idea that female hormones that regulate production of corticotrophin-releasing factor can play the key role in hyperactivity of the hypothalamic-pituitary-adrenal axis, while changes in their level determine the severity of the stress reaction and is a risk factor for depression development [15]. Worse learning of experimental females in comparison with experimental males can be associated with higher sensitivity of females to the development of depression-like behavior [14].…”
Section: Resultssupporting
confidence: 88%
“…However, we found that target genes for CREB/ATF were significantly downregulated in women with trauma exposure and PTSD, indicating decreased CREB/ATF signaling in monocytes in the female sample. Sex hormone differences may influence stress effects on CREB and thereby influence the expression of target genes for CREB/ATF [28,29,55]. However, it is also possible that differences in trauma exposure between the male and female control groups contributed to the findings.…”
Section: Discussionmentioning
confidence: 93%
“…There is a rapidly expanding literature in animal models indicating that there are sexually dimorphic responses to stress and adversity [122,123,124] including and perhaps especially associated with stress during the prenatal period [125,126,127]. In the study of human FHR responses to external stimulation reported above [44], we discovered that female fetuses displayed more mature responses than males at 31 and 36 gestational weeks.…”
Section: Sex-specific Programming Effectsmentioning
confidence: 98%